RELEVANSI NILAI INFORMASI AKUNTANSI: STUDI KOMPARASI ANTARA SAHAM SYARIAH DAN SAHAM NON-SYARIAH DI BURSA EFEK INDONESIA (PERIODE 2013-2016) - Purnama Siddi (INVENTORY: JURNAL AKUNTANSI, 2019)
Stocks in the Indonesia Stock Exchange that enter into the list of Shariah securities (DES) tend to increase over time. This study aims to examine whether Sharia shares have an impact on the value relevance of accounting information. The test was conducted using 1,070 observations consisting of 852 sharia shares and 218 non-sharia shares included in the non-financial sector. Comparison is done by testing the influence of book value per share (BVPS) and earnings per share (EPS) on stock market price (PRICE). The result of the research shows that (1) BVPS has a positive effect on PRICE but only for sharia shares, so the value relevance of BVPS for sharia stocks is higher than the value relevance of BVPS for non-sharia stock. (2) EPS has positive effect on PRICE both for sharia stock and for non-sharia stocks, but the effect of EPS on PRICE is higher for non-sharia shares.